Potential of the Fungus Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae) as an Endophytic Fungus for the Growth of Yardlong Bean (Vigna sinensis L.) - Muhammad Raihan Naufal; Ramadhani Mahendra Kusuma; Arika Purnawati (Bioscientist : Jurnal Ilmiah Biologi, 2026)
The main objective was to determine the effectiveness of this technique in establishing endophytic colonies and its impact on plant vegetative growth. The experiment was conducted in the laboratory and greenhouse using a Completely Randomized Design (CRD) approach. We tested four levels of conidial density: control (no conidia), 1×10⁶, 1×10⁷, and 1×10⁸ conidia per mL, with each replicated five times. Parameters we observed included root and stem colonization success, plant height, and leaf number. Data were analyzed using ANOVA followed by a HSD test at the 5% level. The results showed that B. bassiana is able to enter and develop internally within root and stem tissues. Interestingly, the highest colonization occurred at the lowest concentration (1×10⁶ conidia per mL), with 83.3% in roots and 66.7% in stems. Although statistically, differences in concentration did not always have a significant effect on plant height and leaf number, numerically, inoculated plants showed better growth than controls, especially at 28 days after planting. From these findings, we conclude that soil application of B. bassiana is quite effective in establishing endophytic colonies without disrupting vegetative growth. In other words, this method is worth considering as part of a more environmentally friendly and sustainable pest management strategy.